EXPLORING ENGLISH LANGUAGE ACQUISITION: A STUDY OF CHILDREN USING PICTURE CARDS IN THE HOME ENVIRONMENT - Risa Uswatun Hasanah; Muhammad Anjar Nugraha; Dody Wahyudi Purnama (Bajang Institute, 2026)
This investigate dives into the adequacy of picture cards as a instrument for children's English dialect securing inside the domestic setting, tending to the developing request for casual and intelligently dialect learning past the conventional classroom. Utilizing a graphic subjective approach, the ponder included 3 to 5 children matured 7-9 a long time and their guardians, with information collection crossing three weeks through perception, interviews, and recordings of learning sessions. The discoveries reliably uncovered that picture cards altogether encouraged lexicon advancement, made strides elocution, and boosted learner inspiration, empowering children to lock in with the English dialect in a important and lively way. A basic perspective highlighted was the fundamental association of guardians, who were instrumental in developing a loose and conducive air for learning. This strong environment permitted children to investigate the dialect at their possess pace and successfully diffused the uneasiness regularly related with dialect procurement. The think about emphasizes the control of joining every day settings to empower dialect learning, advertising down to earth bits of knowledge into casual dialect securing and giving important tips for guardians to successfully bolster their children's English learning travel at domestic. Eventually, this inquire about underscores the potential of basic, available devices like picture cards, coupled with dynamic parental cooperation, to make compelling and pleasant dialect learning encounters for children in their claim homesAbstracts are made in two languages, English and Bahasa Indonesia. Abstract more about background, purpose, up to, the results of research, and manai research. Abstract contains up to 250 words, single write spaces with italics (Italics) for English abstracts. Below the abstract are listed keywords consisting of six words, where the first word is again the forward. Abstract in Indonesian can be a translation of an English translation. Tiff editor for abstract syncing for reasons of abstract content.